APPROACHING THE TRANSFORMATIVE JOURNEY IN THE FORTY RULES OF LOVE - Zulaikah, Zulaikah; Kurniati, Nia; Widyani, Julia; Magdalena, Silvia (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2025)
This study aims to explore the transformative journey of Ella Rubinstein, the protagonist of Elif Shafak's The Forty Rules of Love, focusing on her psychological and emotional evolution as she grapples with existential crisis, unfulfilling relationships, and societal expectations. Using a qualitative analysis of Ella’s evolving character, this study examines how her exposure to Rumi's philosophies, through her correspondence with A.Z. Zahara, catalyzes her journey of self-discovery and redefines her understanding of love and identity. By analyzing key themes such as the conflict between societal norms and individual desires, this study uncovers how Ella's awakening reflects broader questions of autonomy, love, and self-actualization. The results suggest that love, as a transformative force, can transcend conventional boundaries and empower individuals to redefine their identities beyond traditional roles, offering a critique of contemporary views on love and relationships. This case study contributes to the broader discourse on personal empowerment, challenging ingrained beliefs and highlighting the power of love in facilitating meaningful life changes.